Construction and Analysis of Coexpression Network to Understand Biological Responses in Chickens Infected by Eimeria tenella - Liu, Baohong; Ma, Xueting; Cai, Jianping (Frontiers in Veterinary Science, 2021)
Coccidiosis, caused by various Eimeria species, is a major parasitic disease in chickens. Our understanding of how chickens respond to coccidian infections is highly limited at both the molecular and cellular levels. In this study, coexpression modules were identified by weighted gene coexpression network analysis in chickens infected with E. tenella. A total of 15 correlation modules were identified using 5,175 genes with 24 chicken samples, 12 with primary and 12 with secondary E. tenella infection. The analysis of the interactions between these modules showed a high degree of scale independence. Gene Ontology and Kyoto Encyclopedia of Gene and Genomes enrichment analyses revealed that the genes in these functional modules were involved in a broad categories of functions, such as immune response, cell cycle, cellular responses to lipids, sterol biosynthetic processes, and RNA transport. Two modules viz yellow and magenta and three genes viz IFNG, IRF1 and CAPZA1 were identified significantly associating with infection status. Preservation analysis showed that most of the modules identified in E. tenella infections were highly or moderately preserved in chickens infected with either E. acervulina or E. maxima. These analyses outline a biological responses landscape for chickens infected by E. tenella. And also indicated that infections with these three Eimeria species elicit similar biological responses in chickens.